Pigments and Dyes in Archaeological and Historical Objects-Scientific Analyses and Conservation Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book presents a collection of original scientific studies aimed at identifying the pigments and dyes in several archaeological or historical objects and artworks. The objects under investigation span from ancient Greek vases to modern paintings, and show the importance of scientific analysis not only to reveal the artists’ materials in different contexts, but also to support conservation and curatorial strategies for the preservation and display of cultural heritage.